Increasing Mangrof Leaves Meal Allowance in Layers Diets Through Enhancing its Nutritive Value - Al-Harthi, M.A. (International Journal of Poultry Science, 2006)
The objective of this study was to improve the nutritive value of mangrof leaves meal in order to increase its allowance in layer diets. The meal was subjected to boiling in an attempt to improve its nutritive value. The study also included testing the effect of supplementing the experimental diets containing the mangrove meal (boiled or raw) with Natugrain or a mixture of spices on laying performance and biological responses associated with egg production. Four hundred and fifty 30- week old Hy-line laying hens were randomly distributed to 15 groups each contained 5 replicates of 6 hens under the same environmental conditions throughout the period of 20 wks. Dietary treatments included 3 levels of either raw or boiled mangrof leaves meal (0, 5 and 10%) for 30 minutes. Each group was received one of these diets and with or without Natugrain and/or spices mixture. Diets were formulated to be isocaloric and iso-nitrogenous. Laying performance, quality of fresh and stored eggs (stored for one month in the refrigerators), intestinal characteristics, chemical composition of eggs and cholesterol contents of yolk as well as some blood plasma constituents were determined. Results obtained showed that mangrof leaves meal contains reasonable amount of the essential nutrients which play an important role in layers nutrition. Boiling process had an enhanced effect on the nutritive value by converting the deleterious materials to less toxic form. Mangrof leaves meal at level of 5% had no adverse effect on body weight gains of Hy-line hens during the laying period. However, increasing dietary Mangrof leaves to 10% adversely reduced weight gain by 19.7% compared to control group. Irrespective of Mangrof meal and feed additives, boiling treatment had no effect on weight gain of laying hens during 30-49 wk of age. Also, regardless of mangrove meal and boiling treatment, only Natugrain® increased weight gain by 24 and 9.6% compared to the negative control and spices supplemented group, respectively. Increasing inclusion level of mangrof leaves meal up to 10% significantly decreased laying rate percentage and egg mass during most of the experimental periods. Also, boiling or adding the feed additives did not stop this reduction. Irrespective of boiling treatment and feed additives, Mangrof leaves meal had no significant impact on egg weight during 30- 49 wk of age. Neither inclusion levels of the tested material nor boiling process nor Natugrain and spices supplementation had an enhancing effect on feed intake. Consequently, feed conversion was the worst as feeding diets containing un-boiled or boiled mangrof meal at level 10%. The impairment in FCR amount to 10.7% compared to control group. The opposite was true with feed additives supplementation which showed an enhanced effect. Increasing dietary mangrof leaves meal up to 10% significantly improved Haugh unit score, yolk color and shell thickness of fresh eggs and those stored for 30 days in the refrigerator, whilst there is different trend with yolk index. Boiling treatment and feed additives supplementation had no significant effect on egg quality traits. Also, mangrof meal levels, boiling process and feed additives had no adverse effect on chemical composition of egg components and plasma constituents. There were no significant interactions between Mangrof meal and boiling treatment and / or feed additives on rate of laying, egg weight, egg mass, feed intake and feed conversion. However, there is a trend for rate of laying, egg mass and feed conversion to improve when Natugrain® or mixture of different spices were added to diet containing 10% of boiled Mangrof leaves. Also, similar finding was observed with the parameters of fresh egg quality of 41 or 49 wk-old hens and those stored in the refrigerators as well as those of intestinal characteristics and reproductive organs. 7-There was a significant effect as feeding boiled Mangrof leave meal-containing diet on plasma albumin, total lipids and yolk protein. Yolk lipid showed an opposite trend to that shown in yolk protein. In general, it may be recommended to incorporate mangrof leaves meal at level 5% as a non-traditional ingredient in laying hen diets without adverse effect on their performance in order to get higher economic return as well as to control excessive body fat deposition and to improve productive and reproductive performance.